Orbit properties of massive prolate galaxies in the Illustris simulation. Issue 3 (4th December 2018) - Wang, Yougang; Mao, Shude; Li, Hongyu; Xu, Dandan; Chen, Xuelei; Springel, Volker
ABSTRACT: We explore orbit properties of 35 prolate-triaxial galaxies selected from the Illustris cosmological hydrodynamic simulation. We present a detailed study of their orbit families, and also analyse relations between the relative abundance of the orbit families and the spin parameter, triaxiality, the ratio of the angular momentum, and the baryon fraction. We find that box orbits dominate the orbit structure for most prolate-triaxial galaxies, especially in the central region. The fraction of irregular orbits in the prolate-triaxial galaxies is small, and it increases with galaxy radius. Both the x -tube and z -tube orbits are important in prolate-triaxial galaxies, especially in the outer regions. The fraction of box orbits for prolate-triaxial galaxies (0.7 < T < 1) decreases with the triaxiality of the stars, while the fraction of x -tube orbits increases with the triaxiality for a given axis ratio. The fraction of box orbits increases and the fractions of x -tube and z -tube orbits weakly decrease with increasing baryon fraction. These results help to understand the structure of prolate-triaxial galaxies and provide cross-checks for constructing dynamical models of prolate-triaxial galaxies by using the Schwarzschild or the made-to-measure methods.